VOLUME DAN KAPASITAS MUAT PALKA KAPAL TUNA LONGLINE TIPE TAIWAN DAN BAGAN SIAPI-API DI PELABUHAN PERIKANAN NIZAM ZAHMAN, JAKARTA - Laila Lafi; Yopi Novita (Buletin PSP, 2008)
This paper discusses about the volume and capacity of fish hold in fishing vessel. By using these values, estimation of fishing vessel productivity can be carried out. In the scope of responsible and sustainable fisheries, knowledge fishing vessel productivity plays an important role in order to avoid under exploitation or over fishing in fishing ground. The aims of the research are to calculate the volume and capacity of fish hold of 50 – 100 GT tuna long liner. One of the result show that the total capacity of fish hold depends on its volume and combination of fish storing system applied.